CYBER SECURITY: CONTEMPORARY CYBER THREATS AND NATIONAL STRATEGIES - Oruj, Zahid (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article is devoted to the study of the basic strategies and doctrines of cyber security and cyber threats. Cyber-attacks have become as commonplace as the Internet itself. Each year, industry reports, media outlets and academic articles highlight this increased prevalence, spanning both the amount and variety of attacks and cybercrimes. It is noted that today information security and cyber security in official documents -concepts, doctrines, charters-of many countries are considered to a large extent as independent concepts that are not related (or very slightly related) to each other, and information security and cyber security are considered as independent areas of activity, little intersecting with each other. This artificial division is due to the fact that in the special services of these countries, information security is mainly carried out by operational agents, whose main tool is operational combinations on the channels of open telecommunication networks and cybersecurity is carried out by technical and operational-technical workers (including hacker programmers, hardware specialists, etc.), whose main form of activity is cyberattacks on the protected information resources of the enemy. Purpose of the research: improvement of the scientific and methodological theoretical and legal foundations of cyber security. Research method: a comprehensive theoretical and comparative analysis of the current legislation of foreign countries and Azerbaijan in conjunction with an analysis of law enforcement practice. Results: the features of the legal regulation of cyber security in Russian and foreign legislation are shown, highlighted the main properties of the concept of cybersecurity.